(untitled) (Global Journal of Human-Social Science, 2021)
International trade agreements were linked to improving labor standard in garment sector in Cambodia Workers in the garment sector are mostly female migrant workers from rural parts of the country This paper aims to answer the following research questions How has COVID-19 affected the right to health of garment workers in Cambodia And what are the risk factors for such workers A field survey with a sample of 316 workers using purposive and snowball methods was conducted between late October and mid-November through interviews using a questionnaire in three different regions Phnom Penh the provincial town of Takeo and two rural villages in Kdanh commune Preykabass district of Takeo province Cambodia s garment workers face a lot of occupational risks and health issues such as body pain after work flue and traffic related accidents in addition to sanitation related health problems Our analysis of the health risks of garment workers using logistic regression suggests that buying lunch at the factory gate or outside living in rented rooms and drinking alcohol were among the causes of falling sick